Framing theory. The media and the transmission of meanings - Amadeo, Belén (2022)
The relation between media and society imply constant interaction. This on going and dynamic interaction is described and explained by the framing theory. Though many authors have written on the matter, the present work makes a new contribution: it systemizes academic production and delivers an integrated outlook of the transmission process. As a matter of fact, media transmits and redefines social dialogue while influencing the perspective from where they present and define issues of public debate.